Hubungan Tingkat Stres dengan Kejadian Sleep Paralysis Pada Mahasiswa Preklinik Fakultas Kedokteran Universitas Nusa Cendana selama Pandemic Covid-19 - Saini, Pasya Putra Pratama Ali (Cendana Medical Journal, 2024)
Background: The phenomenon of COVID-19 pandemic brings a lot of significant changes in the world, these changes are seen as new stresor that increase the prevalence of stress in the world. Medical students are known for having larger prevalence of stress compare to other students due to its complex and difficult education systems. One of the consequence of the high number of stress is the high prevalence of sleep disorders as well. Sleep disorders can effect the academic life of medical students. One of the most common sleep disorder is sleep paralysis that defines as a condition where your mind is awake but you can’t move your body for a moment. Objective: To determine the correlation of stress levels and sleep paralysis incidence on preclinical students Medical Faculty of Nusa Cendana University. Methods: The methods that used in this study is analytical observasional with cross sectional approach. This study conducted on preclinical students Faculty of Medicine, Nusa Cendana University. The data were collected using questionnaire of The Depression Anxiety Stress Scale (DASS 42) and sleep paralysis questionnaire from previous study based on theory. The samples were chosen using accidental sampling technique with 107 respondents from three different batches, 2018, 2019 and 2020 that fulfilling the criteria of inclusion and exclusion. This study was analyzed by univariate and bivariate using the chi square test. Results and Discussion: From this study,out of 107 respondents as many as 19,6% respondents have severe stress level, 21,5 % was medium stress, 19,6% was light stress and 39,3% have no stress, besides that, it is found that 70,1 % of the respondents had sleep paralysis and 29,9% had not sleep paralysis. The result of chi square test shows the result of p=0,000 (p<0,05). Conclusion: There is a significant correlation between stress level and incidence of sleep paralysis on preclinical students Medical Faculty of Nusa Cendana University during COVID-19 pandemic. Keywords: Stress Level, Sleep Paralysis, Medical Student